Heritability and Genetic Causation. - Oftedal, Gry (Philosophy of Science, 2005)
The method in human genetics of ascribing causal responsibility to genotype by the use of heritability estimates has been heavily criticized over the years. It has been argued that these estimates are rarely valid and do not trace genetic causation. Recent contributions strike back at this criticism. I present and discuss two opposing views on these matters represented by Richard Lewontin and Neven Sesardic. I suggest that the conflicting perspectives are based in differing concepts of genetic causation and differing motivations and contexts of discussion. I use the distinction between structuring and triggering causes to clarify the basis for the opposing views.